Verification of training of future masters of physical culture and sports for activities in the conditions of the fitness center - Petro Dzhurynsky; Sofiya Vorobyova; Olena Khomyakova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: verification of the effectiveness of training future masters in physical culture and sports for professional activity in a fitness center. Material and methods: questioning, testing; pedagogical experiment; statistical methods, factor analysis. The study involved 34 applicants for the second (master's) level of higher education 1-2 years of study, educational and professional program (EPP) «Physical culture and sports», specialty 017 «Physical culture and sports». In order to determine the effectiveness of training future masters in physical culture and sports for professional activity in a fitness center, a survey was carried out of applicants for the second (master's) level of higher education; the levels of readiness formation of future masters in physical culture and sports for professional activity in a fitness center. Results: after the completion of the formative stage of the pedagogical experiment, the indicators characterizing a high level of readiness for professional activity in a fitness center increased among applicants in the control group from 7,34% to 11,20%, among applicants in the experimental group from 8,44% to 24,12%. Accordingly, the data characterizing a sufficient level of readiness for professional activity has changed - in the control group from 44,47% to 52,55%, in the experimental group from 49,31% to 68,22%. The data characterizing the elemental level of formation of readiness for professional activity decreased in the control group from 48,19% to 36.25%, in the experimental groups from 42,25% to 7,66%. At the end of the pedagogical experiment, the most significant structural components of readiness were the motivational component; cognitive-reflexive component; personality and activity component. Conclusions: the effectiveness of training future masters in physical culture and sports for professional activity in a fitness center has been determined and tested; the structure of training future masters in physical culture and sports for professional activity in a fitness center has been improved; the provisions for the development and design of the content of the physical culture and sports for the preparation of future masters of physical culture and sports have been improved; the criteria and levels of the readiness formation of future masters in physical culture and sports for professional activity in the conditions of a fitness center.